2013
DOI: 10.1007/s11908-013-0360-2
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin for Antibiotic Treatment in Intensive Care Unit Patients

Abstract: Procalcitonin (PCT), a 116-aminoacids prohormone, has been substantially studied over the last 2 decades in the field of sepsis. Disappointingly low sensitivity values led to the abandonment of the concept of it as a diagnostic tool and then to its being considered more as a prognostic marker with a good correlation with severe infection. Later on, growing concerns about multidrug-resistant bacteria in the ICU environment and about the cost and side effects of antibiotics suggested that PCT might prove to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In intensive care unit, two trials in adult patients have studied antibiotic initiation based on procalcitonin (PCT)-guided algorithms. One study found no effect, and although the other found a significant reduction in antibiotic use,53 a 53% non-compliance in the PCT arm raised concerns about generalisability of the study 51 53 54. One trial in neonates found the addition of interleukin 8 (≥70 pg/mL) to standard management (clinical signs and C-reactive protein (CRP) >10 mg/L) among 1291 NICU admissions resulted in a reduction of antibiotic initiation for suspected EOS from 49.6% to 36.1% (p<0.001) without any ‘missed’ infections 55.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
“…In intensive care unit, two trials in adult patients have studied antibiotic initiation based on procalcitonin (PCT)-guided algorithms. One study found no effect, and although the other found a significant reduction in antibiotic use,53 a 53% non-compliance in the PCT arm raised concerns about generalisability of the study 51 53 54. One trial in neonates found the addition of interleukin 8 (≥70 pg/mL) to standard management (clinical signs and C-reactive protein (CRP) >10 mg/L) among 1291 NICU admissions resulted in a reduction of antibiotic initiation for suspected EOS from 49.6% to 36.1% (p<0.001) without any ‘missed’ infections 55.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
“…The effects of antibiotics for treatment of sepsis can be assessed by monitoring PCT level, determining whether antibiotics should be continued or changed. PCT-guided decision making for suspected early-onset sepsis can safely reduce the duration and the using dosages of antibiotic treatment [5,10,11].…”
Section: Discussionmentioning
confidence: 99%